Monte Carlo Simulation as a Tool for Tunneling Planning - Vargas-Norambuena, J; Perez-Cortes, S (2014)
Underground mining involves development of shafts, ramps, drives or other types of excavation to gain access to mineralized zones and later to serve as the infrastructure for mining. Therefore, the time taken to access the excavation becomes a critical factor in mine planning. This work proposes a simulation algorithm based on stochastic probabilistic methods that can provide the best estimation for the opening excavation times when considering the classic methods of drilling and blasting.The proposed methodology is based on stochastic numerical methods, specifically, the Monte Carlo simulation method, together with the technical conditions that affect the tunnel excavation cycle; the simulation is developed using a computational algorithm.To use the Monte Carlo method, the unit operations involved in the underground excavation cycle are identified and assigned probability distributions that, by means of random number generation, make it possible to simulate the total excavation time.The results obtained by this method are compared with a real case, where it can be seen that the times obtained by the simulation are a better fit with the real tunnel construction times than those planned by means of conventional methods. The simulation results generate different scenarios which contain important parameters to use in the decision making in the planning process. © 2013 Elsevier Ltd.